1992
DOI: 10.1212/wnl.42.10.1888
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of myasthenia gravis in central and western Virginia

Abstract: We conducted a study of the epidemiology of myasthenia gravis (MG) in four locations in central and western Virginia from 1970 through 1984. The population surveyed was 555,851 in 1984. A total of 73 new cases of MG occurred during the survey period, producing an overall average annual incidence rate of 9.1 per million. The point prevalence rate in 1980 was 13.4 per 100,000, and in 1984 it was 14.2. Approximately 15% of the population was black, and we found that incidence and prevalence rates for the black po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 0 publications
12
68
3
4
Order By: Relevance
“…8 The only other study to report the incidence of myasthenia gravis in a North American population was Phillips et al, which reported a total population incidence for all ages (pediatric and adult) of 9.1 per 1 million total population. 2 Among the patients presented by Phillips et al, 4.2% were between 0 and 9 years of age at presentation and 9.5% were between 9 and 19 years of age at presentation. 2 The majority of previous studies describing the incidence of myasthenia gravis relied on retrospective chart reviews from European countries.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8 The only other study to report the incidence of myasthenia gravis in a North American population was Phillips et al, which reported a total population incidence for all ages (pediatric and adult) of 9.1 per 1 million total population. 2 Among the patients presented by Phillips et al, 4.2% were between 0 and 9 years of age at presentation and 9.5% were between 9 and 19 years of age at presentation. 2 The majority of previous studies describing the incidence of myasthenia gravis relied on retrospective chart reviews from European countries.…”
Section: Discussionmentioning
confidence: 89%
“…2 Among the patients presented by Phillips et al, 4.2% were between 0 and 9 years of age at presentation and 9.5% were between 9 and 19 years of age at presentation. 2 The majority of previous studies describing the incidence of myasthenia gravis relied on retrospective chart reviews from European countries. 9 None of the previous studies focused on the incidence of pediatric myasthenia gravis but rather all ages with subsequent division into age groups.…”
Section: Discussionmentioning
confidence: 89%
“…In this disease the thymus plays an important role in the induction of the anti-AChR antibodies, and at the present time total thymectomy is accepted as a standard therapy irrespective of associated thymoma, particularly for the generalized type (1,2). Although typical MG is likely to develop in the second to fourth decades (1), the number of elderly patients with this disease has recently increased in Japan as well as in Europe and the United States (3)(4)(5)(6). Because elderly-onset MG patients without thymoma are considered to commonly show extensive fat infiltration in the thymus, it remains unclear whether total thymectomy is the best therapeutic option for these patients or not.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos autores relata que a doença pode ter início em qualquer idade, desde recém-nascidos até indivíduos com mais de 70 anos [2][3][4]6,8,10,[12][13][14][15]20,23,24,26,27,43 . Assis estudou 372 pacientes com média de idade de 23 anos para sexo feminino e 30 anos para o masculino 1 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…A prevalência da miastenia grave é mostrada na literatura com diferentes taxas que variam de 0,5 a l4,2:100.000 habitantes. A incidência varia de 2.0 a 10.4:1.000.000 habitantes 3,9,[21][22][23][24][25][26] . A doença pode ocorrer em qualquer faixa de idade, do nascimento aos 80 anos, tendo maior comprometimento aos 26 anos nas mulheres e 3l anos nos homens.…”
unclassified